Specific insulin and proinsulin in normal glucose tolerant first-degree relatives of NIDDM patients - Coifman,R. (1999)
In order to identify early abnormalities in non-insulin-dependent diabetes mellitus (NIDDM) we determined insulin (using an assay that does not cross-react with proinsulin) and proinsulin concentrations. The proinsulin/insulin ratio was used as an indicator of abnormal ß-cell function. The ratio of the first 30-min increase in insulin to glucose concentrations following the oral glucose tolerance test (OGTT; I30-0/G30-0) was taken as an indicator of insulin secretion. Insulin resistance (R) was evaluated by the homeostasis model assessment (HOMA) method. True insulin and proinsulin were measured during a 75-g OGTT in 35 individuals: 20 with normal glucose tolerance (NGT) and without diabetes among their first-degree relatives (FDR) served as controls, and 15 with NGT who were FDR of patients with NIDDM. The FDR group presented higher insulin (414 pmol/l vs 195 pmol/l; P = 0.04) and proinsulin levels (19.6 pmol/l vs 12.3 pmol/l; P = 0.03) post-glucose load than the control group. When these groups were stratified according to BMI, the obese FDR (N = 8) showed higher fasting and post-glucose insulin levels than the obese NGT (N = 9) (fasting: 64.8 pmol/l vs 7.8 pmol/l; P = 0.04, and 60 min post-glucose: 480.6 pmol/l vs 192 pmol/l; P = 0.01). Also, values for HOMA (R) were higher in the obese FDR compared to obese NGT (2.53 vs 0.30; P = 0.075). These results show that FDR of NIDDM patients have true hyperinsulinemia (which is not a consequence of cross-reactivity with proinsulin) and hyperproinsulinemia and no dysfunction of a qualitative nature in ß-cells.